Quantificação e distribuição do estoque de biomassa acima do solo em floresta estacional decidual - Trautenmuller, Jonathan William (2015)
This study aims to quantify and analyze the distribution of the stock of above-ground biomass in Deciduous Forest fragments (FED) in the Region of the Northwest RS, generating the necessary information to support the development of forestry projects. Thus, we installed seven sampling unit of 12 x 12 m with subunits of 5 x 5 m and 1 x 1 m to quantify the natural regeneration classified as Stratum 1 (E1), 2 (E2) and 3 (E3), the E1 is composed of plants with less than 1.3 m from the ground, the E2 all vegetation with over 1.3 m in height and less than 5 cm diameter at breast height (DBH) and E3 all vegetation with DBH between 5 and 10 cm. In the main units all vegetation with more than 10 cm DBH were classified as stratum 4 (E4). For quantification of biomass above ground, after the overthrow of the trees, all tree vegetation was weighed directly in the field, with split trunk (wood with bark), thick branches (diameter greater than 5 cm), thin branches (diameter less than 5 cm), and miscellaneous sheets, these being identified at the species level. To estimate the biomass of the allometric models adjustments were collected the following information dendrometric E4 diameters at 0 (baseline), DAP, 25, 50, 75 and 100% of morphological inversion point height (HPIM) of height HPIM, total height. To estimate the above-ground biomass of different specific gravity methods (MEB) was obtained from wood and other literature were calculated from the disks taken at the time of the DAP, these disk, shelled, had approximately 2 cm thick. The results indicated that the average stock of biomass for the FED was 371.1 Mg.ha-1. The trees with the breast height diameter (DBH) greater 10 cm accounted for over 89% of the biomass (4759 kg). To build the allometric models, the equations adjusted without stratification, have adjusted coefficient of determination (R2aj.) Between 0.726 to 0.972 and standard error of estimate in percentage (Sxy%) ranging from 33.5 to 119.6, the best adjusted model, for not stratified data set was obtained by the stepwise procedure, represented by the following equation: PST = β0 + β1.(DAP3) + β2.H + β3.(DAP3.H), with R2aj.. 0.972 and Sxy 33.5%. For the stratified, only diameter class above 15 cm of acceptable parameters, R2aj. 0.968 and Sxy 26.8%. For the estimation of biomass by different methods, the direct method has accumulated 11,450 kg bole biomass (PSF) for the seven installments. The indirect method that is closer to the PSF was the biomass obtained from the volume of the equation and the MEB arithmetic average of 13,141 kg, and the one with the biggest difference was obtained by rigorous and volume weighted average MEB, which totaled 20,060 kg, and arithmetic mean MEB differed from the PSF by Dunnett's test at 5% probability. It is recommended reliable quantification of above-ground biomass in stratum E4, especially the larger ones, as they may provide greater error in the quantification and estimation of forest biomass.